Genome analysis of Phytophthora cactorum strains associated with crown- and leather-rot in strawberry - Gogoi, Anupam; Rossmann, Simeon L.; Lysøe, Erik; Stensvand, Arne; Brurberg, May Bente (Frontiers in Microbiology, 2023)
Phytophthora cactorum has two distinct pathotypes that cause crown rot and leather rot in strawberry (Fragaria × ananassa). Strains of the crown rot pathotype can infect both the rhizome (crown) and fruit tissues, while strains of the leather rot pathotype can only infect the fruits of strawberry. The genome of a highly virulent crown rot strain, a low virulent crown rot strain, and three leather rot strains were sequenced using PacBio high fidelity (HiFi) long read sequencing. The reads were de novo assembled to 66.4 -67.6 megabases genomes in 178-204 contigs, with N50 values ranging from 892 to 1036 kilobases. The total number of predicted complete genes in the five P. cactorum genomes ranged from 17,286 to 17,398. Orthology analysis identified a core secretome of 8,238 genes. Comparative genomic analysis revealed differences in the composition of potential virulence effectors, such as putative RxLR and Crinklers, between the crown rot and the leather rot pathotypes. Insertions, deletions, and amino acid substitutions were detected in genes encoding putative elicitors such as beta elicitin and cellulose-binding domain proteins from the leather rot strains compared to the highly virulent crown rot strain, suggesting a potential mechanism for the crown rot strain to escape host recognition during compatible interaction with strawberry. The results presented here highlight several effectors that may facilitate the tissue-specific colonization of P. cactorum in strawberry.